Strengths and Challenges of Distance Learning Modalities in the New Normal: Basis for Intervention Program - Hernandez, Laura (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
The study was conducted to identify the strengths and challenges of distance learning modalities as a basis for intervention programs from a memorial high school in a schools’ division in Bulacan, Philippines. The researcher used a descriptive survey type of study. For the sample of the study, it employed eight (8) teachers and 39 learners from a junior high school chosen randomly. A self-made checklist survey questionnaire was created by the researcher which was validated by a panel of experts. Descriptive statistics were used to analyze the collected data with the help of a Microsoft Excel sheet. Results revealed that teachers and learners have a variety of strengths in distance learning modalities. In addition, teachers and learners also stressed the different challenges they encountered for distance learning modalities. Based on these findings of the study, the researcher used them for a possible formulation of an intervention program that aimed to providing solutions for the challenges of distance learning and also enhancing the strengths for both the teachers and learners.